Characterization of a MERS-related betacoronavirus in Danish brown long-eared bats (Plecotus auritus) - Camille Melissa Johnston; Vithiagaran Gunalan; Hans J. Baagøe; Anna S. Fomsgaard; Charlotta Polacek; Morten Rasmussen; Louise Lohse; Thomas Bruun Rasmussen (Virology Journal)
Abstract Background Bats are recognized as natural reservoir hosts for numerous viruses and are believed to be the evolutionary origin of alpha- and beta-coronaviruses (CoVs), such as SARS-CoV, SARS-CoV-2, and possibly MERS-CoV. MERS-related beta-CoVs have been identified in bat species from Africa, America, Asia, and Europe. In this study, we describe the first detection and characterization of a MERS-related beta-CoV in Danish brown long-eared bats (Plecotus auritus). Methods Fecal samples collected through a national surveillance program were screened using pan-CoV RT-qPCRs. Positive samples underwent ORF1b sequencing, microarray analysis and Illumina MiSeq sequencing, followed by metagenomic assembly of full-length genomes. A global phylogenetic tree was used to determine placement within the Coronaviridae family and local maximum likelihood phylogenetic analysis clarified subgroup placement. The receptor-binding potential of the spike protein to human DPP4, ACE2, and bat ACE2 orthologs was assessed through phylogenetic analysis of the receptor-binding domain (RBD), alongside homology modeling and structural analysis. Results Three samples tested positive for CoVs. One sample from a Soprano pipistrelle (Pipistrellus pygmaeus) was identified as alpha-CoV by ORF1b sequencing. The remaining two samples, obtained from a colony of Plecotus auritus, were identified as beta-CoVs, and separate microarray results indicated the presence of a MERS-related CoV. Full genomes were successfully assembled using a metagenomic approach. Phylogenetic analysis placed them within the merbecoviruses, forming a distinct clade with viruses detected in Vespertilionidae bats from Western Europe and East Asia. Analysis of the RBD placed them within the HKU25 clade. Structural modeling suggested hydrogen bonding patterns between the RBD and human/bat ACE2 orthologs or human DPP4, similar to known in vitro complexes, indicating potential receptor binding. Conclusion This is the first report of MERS-related beta-CoVs in bats from Denmark. Phylogenetic analyses reveal that these novel viruses belong to the HKU25 clade, a clade with known ACE2 receptor preference. Experimental validation is needed to confirm the receptor-binding potential, as additional interactions at the RBD-receptor interface may differ from previously described bat-merbecoviruses. Continued surveillance is crucial to identify potential intermediate hosts and assess interspecies transmission risk, with focus on the spike protein, receptor specificity, and binding affinity.